Acetylsalicylic Acid - Schrör, Karsten (De Gruyter, 2022)
This book is the first and to date only compendium on the history, pharmacology, toxicology, and clinic of acetylsalicylic acid - not only the best known, but probably the most successful drug in medical history. Written by one of the world's leading experts in the field of aspirin research, it addresses the latest results of research by critically evaluating over 100 studies and summing up collected results from over 40 years of research.